Kinetic Simulation and Parameter Optimization for Glue Pot Lifting Device of YB49 based on ADAMS - Qu Huayin; Fang Xin; Wang Yong (Jixie chuandong)
In order to fulfill glue pot lifting device precise positioning operation within YB49 type cigarette packer,by using the kinematic characteristic of the anti- parallel crank mechanism,the accurate mathematical model of glue pot lifting device is created. The kinetic simulation for the lifting device is carried out by ADAMS parametric design and the sensitivity of the angular rotation function which are received by the simulation would be evaluated and analyzed. The optimization of parameter calculation is carried out with the sequential quadratic programming method in ADAMS and in the end the appropriate size of the mechanism is concluded after the bar lengths of the mechanism and angles are corrected. Finally,the result is approved to be accurate and reliable in the real sample device. The down time of the packer is shortened and the production rate is increased.